Expression of survivin in oral potentially malignant disorders: An immunohistochemical study - Venkatraman R Rajanna; Murali C Raveendranath; Shanmugam Kathiresan; Soundarya Srinivasan; Janani Ilango (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to compare the immunohistochemical expression of survivin in oral potentially malignant disorders (OPMDs) and evaluate its prognostic significance among oral leukoplakia (OL), oral submucous fibrosis (OSMF), and oral lichen planus (OLP). Materials and Methods: The study material consisted of 60 formalin-fixed paraffin-embedded tissue samples: 15 cases each of OL, OSMF, OLP, and normal oral mucosal epithelium as control. Survivin expression was analyzed immunohistochemically, and data analysis was accomplished using Statistical Package for Social Sciences, version 22.0 (SPSS Inc., Chicago, IL). Fisher's chi-square test was opted to compare the study groups. Results: Survivin was expressed in all the OPMDs including OL, OSMF, and OLP, but was absent in normal oral tissue samples. Higher immunoreactivity and survivin staining was observed in OLP compared to OL and OSMF whereas OL showed a significant difference in the distribution of survivin immunoexpression against OLP. An increased nuclear expression of survivin along with distribution in the basal and parabasal layers was evident in all OPMDs. Conclusion: Survivin was expressed more in OLP in comparison to OSMF and OLP, indicating unfavorable prognosis. OL showed increased expression in comparison to OSMF, showing unfavorable prognosis. On the basis of this study, it was concluded that survivin may be used as an important diagnostic and prognostic marker for OPMDs.